A Review of Neovascular Glaucoma: Etiology, Pathogenesis, Diagnosis, and Treatment - Danielė Urbonavičiūtė; Dovilė Buteikienė; Ingrida Janulevičienė (Medicina, 2022)
Neovascular glaucoma (NVG) is a rare, aggressive, blinding secondary glaucoma, which is characterized by neovascularization of the anterior segment of the eye and leading to elevation of the intraocular pressure (IOP). The main etiological factor is retinal ischemia leading to an impaired homeostatic balance between the angiogenic and antiangiogenic factors. High concentrations of vasogenic substances such as vascular endothelial growth factor (VEGF) induce neovascularization of the iris (NVI) and neovascularization of the angle (NVA) that limits the outflow of aqueous humor from the anterior chamber and increases the IOP. NVG clinical, if untreated, progresses from secondary open-angle glaucoma to angle-closure glaucoma, leading to irreversible blindness. It is an urgent ophthalmic condition; early diagnosis and treatment are necessary to preserve vision and prevent eye loss. The management of NVG requires the cooperation of retinal and glaucoma specialists. The treatment of NVG includes both control of the underlying disease and management of IOP. The main goal is the prevention of angle-closure glaucoma by combining panretinal photocoagulation (PRP) and antiangiogenic therapy. The aim of this review is to summarize the current available knowledge about the etiology, pathogenesis, and symptoms of NVG and determine the most effective treatment methods.